Directions In Hydropower : Scaling up for Development - World Bank (World Bank, Washington, DC, 2012)
After a period of stagnation, the story of hydropower infrastructure is changing. Emerging global dynamics are recasting the role and value of hydropower in development, recognizing its potential contribution to a complex web of energy security, water security and regional development and integration. In addition to bringing electricity to the 1.6 billion people who lack access, hydropower offers a hedge against volatile energy prices and can play an important role in energy trade and regional power pools. As a renewable energy resource, hydropower's dual role in climate change mitigation and adaptation is critically important.